POSTCOLONIAL IMMIGRANTS: THE MOLUCCAN DIASPORA IN THE NETHERLANDS - Ismail, Indira (UI Scholars Hub, 2023)
This research provides knowledge about the history of the arrival of the Moluccans to the Netherlands as part of the Dutch East Indies postcolonial immigrants who have now formed a diaspora in the Netherlands. Source tracing was carried out using literature reviews through search engines and keywords related to the research object. The results of the research show that migration, which later turned into integration into Dutch society, underwent a long process that was far from smooth as it had to go through a number of problems both internal (personal and group) and external (Dutch policies).